Turning European XFEL raw data into user data - Schmidt, Philipp; Ahmed, Karim; Danilevski, Cyril; Hammer, David; Rosca, Robert; Kluyver, Thomas; Michelat, Thomas; Sobolev, Egor; Gelisio, Luca; Maia, Luis; Manetti, Maurizio; Malka, Janusz; et al. (Frontiers in Physics, 2024)
The European X-ray Free Electron Laser is a research facility located close to Hamburg, offering X-ray pulses with ultra-high brilliance and femtosecond duration at megahertz repetition rates.The detection systems necessary to unlock the full scientific potential made possible by this machine poses considerable challenges both in terms of data volume and rate, as well as the interpretation of their recorded signal. To provide optimal data quality, expert and detector-specific knowledge not easily accessible to external facility users is essential, and its implementation must cope with the generated volumes.We therefore aim to perform these preparatory processing steps and offer users a dataset suitable for further analysis as the primary data product. This work describes the machinery and workflows providing this data to users in an automatic, configurable and reproducible manner, both online during the experiment, and offline for scientific analysis afterward on the way to publication.